The politics of remembrance in the novels of Günter Grass - Donovan Cole, Alex, author.
1 online resource (140 pages).
Keywords: "This manuscript argues for the importance of Günter Grass as a political thinker in addition to his status as a novelist and public intellectual, capable of forming ethical responses to contemporary issues like neoliberalism and place of the petit bourgeoisie in social life. I define Grass's trajectory as a thinker through his novels and speeches. Primarily, I draw attention to the role memory plays in Grass's thought: that his work represented an intellectual and aesthetic response to the role Nazism continued to play in West German politics in the post war era. To Grass, Nazism represented a resurgent threat unaddressed following the end of World War II. Later, Grass amended his concept of memory politics to address neoliberal capitalism, reiterating his radicalism and affirming the need for German society to resist the rise of extreme ideologies"--